"Traffic intervention" policy fails to mitigate air pollution in megacity Delhi. Issue 74 (August 2017) - Chowdhury, Sourangsu; Dey, Sagnik; Tripathi, Sachchida Nand; Beig, Gufran; Mishra, Amit Kumar; Sharma, Sumit
Highlights: We attempt to quantify whether odd even restriction was able to mitigate ambient PM2.5 concentration using satellite data as well as chemical transport model simulations. We find no clear reduction in ambient PM2.5 during the period of traffic restriction. High concentration of PM2.5 in the surrounding areas of Delhi and its transport may be detrimental to the success of this initiative of odd even traffic restriction. A more comprehensive inter-sectoral and inter-state action plan is required. Abstract: Megacity Delhi has been ranked amongst the top most polluted cities in the world consistently over the last few years (WHO, 2016 ). As a desperate and emergency measure, the administration implemented 'traffic intervention' mitigation effort by instigating 'odd-even' policy as a trial for 15 days in January (1–15) 2016. During this period, odd and even numbered private cars were restricted to respective odd and even days. Here we examine the impact of this policy intervention on ambient particulate matter smaller than 2.5 μm (PM2.5 ) through a combination of in-situ, satellite and model data. Traffic restriction reduces PM2.5 by 4–6% (maximum up to 10% in three local hotspots) which is within the uncertainty range of satellite-based estimates (and hence not detected). This is not a significant result considering the fact that such step was taken as an emergency measure when PM2.5 exposure exceeded 250 μg/m 3 during the winter season. The failure is attributed to stable meteorological conditions (winds are not strong enough to disperse PM2.5 away) during the period and there was no control over PM2.5 outside the periphery of the city. A more comprehensive inter-sectoral and inter-state action plan is required to address this alarming issue in this region.